Ultrasound-guided adductor canal block versus femoral nerve block for arthroscopic anterior cruciate ligament repair under general anesthesia - Poonam S Ghodki; Priyanka S Shalu; Shalini P Sardesai (Wolters Kluwer Medknow Publications, 2018)
Background and Aims: Adductor canal block (ACB) is now an established component of multimodal analgesia for knee replacement surgery and is slowly replacing femoral nerve block (FNB). It is also gaining popularity for providing pain relief in knee arthroscopies including anterior cruciate ligament reconstruction surgery (ACLR). Data is lacking from the Indian subcontinent on comparing ACB to the traditional FNB for ACLR. Hence, we conducted the present study to compare ACB and FNB in ACLR under general anesthesia. Material and Methods: Sixty patients were randomized to receive either ACB or FNB under ultrasound guidance. Postoperatively, quadriceps muscle strength (straight leg raise and time up and go; TUG test) and quality of analgesia (numeric rating scale; NRS and patient satisfaction score) were assessed every 6 hour, and thereafter, up to 48 hours. The time of rescue analgesia and total analgesic consumption (tramadol) were also recorded. Data was statistically analyzed and P < 0.05 was considered to be significant. Results: Patients receiving ACB had significantly less quadriceps weakness (P < 0.001) compared to FNB on postoperative day (POD) 1. In addition, patient satisfaction score was statistically higher (P < 0.05) in FNB on POD1. Both the above parameters were comparable on POD2. No statistically significant difference was recorded in NRS, time for rescue analgesia, and total analgesic consumption among the two groups. Conclusion: ACB preserves quadriceps motor strength while providing analgesia comparable to FNB in patients undergoing ACLR. However, patient satisfaction score is better with FNB than ACB.